MORPHOLOGICAL STRUCTURE AND CHANGES OF THE RENAL CELL CYCLE IN CHRONIC KIDNEY DISEASE AND ITS CORRECTION WITH HYDROGEN SULPHIDE AND GENISTEIN - Voloshchuk, N.I.; Korol, A.P.; Denysiuk, O.M.; Pashinska, O.S.; Taran, I.V.; Sayenko, A.V.; Nefodov, O.O. (World of Medicine and Biology, 2023)
The purpose of the study was to establish the effect of hydrogen sulfide and genistein on cell cycle indicators and histomorphological changes in kidneys under conditions of experimental chronic kidney disease. In sexually mature white non-linear rats, the pathology was modelled by unilateral nephrectomy and subtotal (5/6) resection of the contralateral kidney. Cytometric parameters and renal morphological changes were evaluated after 40 days by DNA flow cytometry and light microscopy, respectively. It was established that the use of the hydrogen sulfide donor NaHS, as well as genistein, showed a pronounced nephroprotective effect due to the antiapoptotic effect, the normalization of the number of mitoses and the activity of DNA synthesis, inhibition of the development of structural and degenerative-dystrophic changes in the kidneys, activation of compensatory-adaptive and regenerative processes and normalization of hemodynamics. This can become the basis for developing more effective pharmacotherapy for chronic kidney disease.